System Information Object Gunungkidul Beach Tourism and Booking Travel Services Using the Laravel Framework - Anwar Fauzi, Muhammad Afif; Rianto; Saputra, Nurirwan (Lembaga Penelitian dan Pengabdian Mayarakat (LPPM) Universitas PGRI Yogyakarta, 2024)
Gunungkidul is famous for with beauty the beach is stunning. However, information about object tour beaches in Gunungkidul is Still scattered and difficult to access for tourists. Apart from that, tourists also experience difficulty in order tourist travel services To visit beaches. Thesis This aims To develop a system information object tour beach Gunungkidul and reservations tourist travel services using the Laravel framework. System This provides complete and accurate information​ about object tour beaches in Gunungkidul, as well as possible traveler order tourist travel services with easy and safe. Study This uses a method combination of Qualitative and quantitative with the Laravel framework system, which is a popular PHP framework For the development of web applications. Laravel provides various convenient features​ of development systems, such as routing, databases, and authentication. Data collection techniques use surveys created online​ with Google Forms. Study This uses waterfall methodology. The waterfall methodology is the methodology development of device linear software and processes sequentially. System This has been tested and proven can walk with Good. System This can help travelers get information about object tour beaches in Gunungkidul and order tourist travel services with ease and safety.